AB0870 Whole body MRI findings of non axial manifestations in early axial spondyloarthritis – results of the esther trial at baseline. (23rd January 2014) - Althoff, C.E.; Hermann, K.G.; Song, I.-H.; Haibel, H.; Rudwaleit, M.; Hamm, B.; Listing, J.; Sieper, J.
Abstract : Background: To evaluate the extend of active inflammation and structural changes in non axial sites in patients with Ankylosing Spondylitis (AS) and non-radiographic axial Spondyloarthritis SpA (nr-SpA) with short disease duration in whole body MRI (wb-MRI). Objectives: To utilise wb-MRI with a comprehensive protocol for the evaluation of both active and structural lesions outside the spine and the sacroiliac joint (SIJ) in nr-axSpA in comparison to AS. Methods: Wb-MRIs of 75 patients (mean age 33±8 yrs.) with early axial spondyloarhtritis (SpA) and a disease duration of <5 years [1] were scored for active inflammatory lesions and chronic changes on STIR and T1 weighted sequences. The anterior chestwall, the pelvic region, the lower extremities and the proximal parts of the upper extremities were evaluated for osteitis/enthesitis (28 sights) synovitis/effusion (12 sights) and erosions (10 joints). Scoring was performed by two blinded radiologists in consensus reading. Results: The study cohort consisted of 39 patients with AS and 36 nr-axSpA patients with similar clinical characteristics. A total of 58 patients (77%) showed signs of active inflammation, either enthesitis/osteitis or synovitis/effusion, outside the spine and the sacroiliac joints. Enthesitis was more frequent in the AS group (n=22) than in the nr-axSpA group (n=12; p<0.05), most frequently at the pelvis. Multilocular enthesitis was significantly more frequent in the AS group compared to the nr-axSpA group (p=0.01). Evidence of peripheral synovitis/bursitis was frequent (59%) with similar extend in both groups. The most frequent locations were the knees (32 patients) and ankle joints (25 patients), followed by the hips (7 patients). No chronic changes were detected at the non axial joints included in the analysis. Conclusions: In this cohort of early axial SpA patients non axial inflammation is a frequent finding with significantly more patients affected in the AS group. Comprehensive wb MRI protocols can image inflammatory changes not covered by dedicated spine and SIJ protocols. References: Song IH, Hermann K, Haibel H, Althoff CE, et al. Ann Rheum Dis. 2011 Apr;70(4):590-6. Disclosure of Interest: None Declared